A Literature Review about One of the Successful Skills of the 21st Century: Collaborative Ability Student - Astiswijaya, Nike; Kusnandi, Kusnandi; Juandi, Dadang (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
One of the most crucial abilities for students to cultivate is the capacity to engage in collaborative endeavours. Despite the growing interest in collaboration as a skill required of students, the context of collaboration itself remains unclear. The objective of this literature review is to examine the conceptualisations, definitions and understandings of collaboration as presented in the research literature. Collaboration can be defined as a process whereby members of a group interact with one another in order to fulfil their roles and to solve problems or achieve goals collectively. In order to achieve this, it is essential that responsibility is shared. The most frequently employed indicators are those identified by Trilling and Fadel, namely cooperation, flexibility, responsibility, compromise and communication. It is incumbent upon educators to consider how the design of assessment tasks can be modified to encourage all students in a group to participate, share thoughts, gather resources and ideas, manage tasks, manage time and communicate effectively.